Migration, diasporas and culture: an empirical investigation - Collier, P; Hoeffler, A (Wiley, 2018)
Using a gravity model we examine the dynamics of migration from developing to OECD countries. Origin and destination countries are characterized by substantial differences in incomes, political rights and cultures. Incentives as well as costs shape the decision to migrate. One powerful dynamic effect is that diasporas increase migration, mainly because they lower the cost of migration. Diasporas assist the next wave of migrants by overcoming the high cost of the emigration, in particular when the origin country is far away and poor. The interaction between the diaspora and cultural distance is also significant. Diasporas in culturally distant countries appear to be particularly useful in overcoming the cost of migration. We interpret this as evidence that culturally distant diasporas are less likely to integrate and maintain closer links with their country of origin, while diasporas from culturally similar countries are more likely to integrate and thus be less useful to potential new migrants.